Faktor-faktor yang mempengaruhi pendapatan petani kopi di Kecamatan Kayu Aro Barat Kabupaten Kerinci studi kasus: Kelompok Tani Sumber Rezeki - Ryan Aditya Rizky; Heriberta; Adi Bhakti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
The main objectives of this research are: First, to know the characteristics of coffee farmers in Kayu Aro Barat District. Second, analyzing the factors that affect the income of coffee farmers in Kayu Aro Barat District. The data used is sourced from the identity of the respondent (sample) and a list of questions (questionnaire) given to the Sumber Sustenance Farmer Group in Pasar Minggu village, Kayu Aro Barat District. The sample used in this study were 55 respondents. The method used to analyze this research is descriptive quantitative. This study uses multiple linear regression analysis based on Ordinary Least Square (OLS). Based on the results of this study, the average farmer is male, with an average age of 51 years and an average marital status of married. The number of dependents with an average of 4 people, Length of work as a farmer with an average of 9 years. The latest education is a farmer with an average high school graduate, with an average income of Rp. 11,772,726, with an average household expenditure of Rp. 3,068,544, and the average production amount is 2.06 tons. The regression results show that the variables of selling price, capital, and land area have a positive and significant effect on the income of coffee farmers in the Sumber Rezeki farmer group in Kayu Aro Barat District, Kerinci Regency.